"Convoluted Journeys": Integrating Nonprofit Organizations and University Science. Issue 3 (4th March 2019) - Crossgrove Fry, Vanessa; Schneider, Jen; Sargeant-Hu, Sally; Anderson, Carl; Olson, Erik
Abstract: University scientists are frequently challenged to embrace stakeholder engagement in a way that departs from traditional contract-oriented relationships; this is occurring within water management across the American West. However, few studies specifically address how university scientists engage nonprofit organizations as stakeholders in collaborative water management research. This manuscript reports on an examination of a key set of stakeholders—nonprofit environmental organizations—with a goal to better understand how such organizations conceptualized, created, and implemented scientific data in water management decision making. The study provides insights into why interactions between university scientists and nonprofits are infrequent and underdeveloped. The project identifies how nonprofit organizations strategically use scientific information across a variety of contexts and for diverse purposes. These practices may sometimes be at odds with how university scientists conceive of or practice science, making stakeholder engagement challenging. The study also provides suggestions for how universities might address some of these challenges.